The Mg related GaN blue luminescence deep level and its connection to an MgO surface state - Or H. Chaulker; Yury Turkulets; Ilan Shalish (Scientific Reports)
Abstract GaN is taking over from silicon in power electronics, but its density of interface states has yet to be adequately controlled. The major step turning GaN into a technological semiconductor was its p-type doping. Mg is currently the only p-type dopant in technological use in GaN. Its incorporation into the lattice is difficult, requiring a thermal treatment that only partially activates the Mg. To achieve moderate p-type doping requires high doses of Mg that mostly remain inactive – a potential for defects. These defects have mostly been studied by photoluminescence that cannot differentiate bulk from surface states. Here, we used an absorption-based spectroscopy, originally invented by the inventors of the transistor – surface photovoltage spectroscopy. The results seem to transform the picture radically as far as our understanding of the famous Mg-associated blue luminescence. We observe an optical transition from the valence band into a deep trap around 0.49 eV above the valence band, along with what appears to be a complimentary transition from the same trap into the conduction band peaking at 2.84 eV (precisely coinciding with the “blue luminescence” energy). The similar shape of the spectra, their complimentary energies within the bandgap, and their opposite nature (hole vs. electron trap), appear to be more than a coincidence suggesting an Mg-related surface state. We suggest that small amounts of surface-segregated Mg oxidize during the post-growth Mg-activation heat treatment forming a surface state. HCl etch is observed to affect the photovoltage at the “blue luminescence”-related energy. A surface treatment is unlikely to affect the bulk. The only case that could support existence of these blue-emitting centers deeper than the surface is when they decorate extended defects – a special case of surface states. Finally, we show that reported luminescence from pure MgO produces the same blue luminescence even at the absence of GaN.